A lithium battery structure and processing technology for electric bicycles

By using additives with specific ratios in lithium batteries to build high-performance SEI/CEI films, the problems of reduced battery life and poor safety performance of lithium batteries under low temperature conditions are solved, and higher low-temperature performance and service life are achieved.

CN119361836BActive Publication Date: 2025-03-28TIANJIN CIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411910640.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The battery life of lithium batteries under low temperature conditions has significantly decreased, resulting in poor battery capacity attenuation and safety performance. This is mainly due to the increased viscosity of the electrolyte and poor wetting properties, the low diffusion coefficient of Li+ in positive/negative electrode materials, and the slow charge transfer and desolvation process, resulting in an increase in the risk of lithium dendrites growth and short circuit.

Method used

A specific ratio of N-N dimethyl trifluoroacetamide, methylene methane disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, hexamethyldisilazane are used as additives to build an SEI/CEI film rich in inorganic components, low impedance, high stability, thin and dense, to improve the performance of lithium batteries under low temperature conditions.

Benefits of technology

It effectively alleviates the problems of low Li+ diffusion coefficient and increased electrolyte viscosity under low temperature conditions, improves the low temperature performance of the battery, ensures the battery capacity retention rate at -40℃ and -85℃, extends the battery service life and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of lithium batteries, and in particular to a lithium battery structure and processing technology for electric bicycles. A lithium battery structure for electric bicycles, comprising a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte, wherein the electrolyte comprises 75-90 parts by weight of an organic solvent, 8-15 parts by weight of a lithium salt, and 1-5 parts of an additive; the additive comprises N-N-dimethyltrifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilylphosphite, and hexamethyldisilazane in a weight ratio of (3-5): (1-2): (0.8-1.2): (1.5-2.5): (1-2). The obtained lithium battery can achieve a battery capacity retention rate of 72-85% at -40°C and a battery capacity retention rate of 42-53% at -85°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium batteries, and in particular to a lithium battery structure and processing technology for electric bicycles. Background Art

[0002] At present, lithium batteries have been widely used in various electronic products, electric vehicles and energy storage devices. As the application of lithium-ion batteries becomes more and more extensive, the performance requirements for lithium-ion batteries are also getting higher and higher.

[0003] In actual use, the battery life of electric bicycles decreases significantly after entering the cold season. This is actually due to the serious capacity decay of lithium batteries. This may be because the viscosity of the electrolyte increases at low temperatures, and the wettability between the electrode material and the diaphragm is poor, resulting in low conductivity. + The diffusion coefficients in the positive / negative electrode materials are low, and the charge transfer and desolvation processes at the battery material interface are slow. In addition, the poor kinetics will lead to large battery polarization (higher overpotential), resulting in Li + Lithium dendrites are more likely to form when embedded in the negative electrode. The growing lithium dendrites will pierce the separator and cause a short circuit, thus affecting the safety and life of the battery.

[0004] In order to improve the low temperature performance of lithium batteries, researchers have often used methods such as doping, surface post-treatment, and special morphology optimization to treat the positive / negative electrode materials, which can improve the low temperature performance of Li + The most effective way to improve the diffusion coefficient in the material is to perform special morphology optimization on the positive and negative electrode materials. Special morphology optimization includes nano-crystalization, preferred crystal orientation, concentration gradient materials, etc. However, changing the material morphology usually affects the processing performance of the material and makes the electrode preparation process more complicated. Therefore, it is extremely necessary to develop more effective methods to improve the low-temperature performance of lithium batteries. Summary of the invention

[0005] In order to improve the low-temperature performance of lithium batteries and enhance the applicability of electric bicycles in cold weather, the present application provides a lithium battery structure and processing technology for electric bicycles.

[0006] In a first aspect, the present application provides a lithium battery structure for an electric bicycle, which adopts the following technical solution.

[0007] A lithium battery structure for an electric bicycle, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein the electrolyte comprises 75-90 parts by weight of an organic solvent, 8-15 parts by weight of a lithium salt, and 1-5 parts of an additive;

[0008] The additives include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of (3-5): (1-2): (0.8-1.2): (1.5-2.5): (1-2).

[0009] When a liquid lithium-ion battery is charged and discharged for the first time, the electrolyte reacts at the solid-liquid interface of the electrode to form a passivation layer covering the surface of the electrode material. This passivation layer is an interface layer that has the characteristics of a solid electrolyte and an electronic insulator, but is also an excellent conductor of lithium ions. Li ions can freely embed and escape through this passivation layer, so this passivation layer is called a solid electrolyte interface, or battery SEI membrane for short. It can be stable in an organic electrolyte solution, and solvent molecules cannot be passivated through this layer, which can effectively prevent the co-embedding of solvent molecules and avoid damage caused by the co-embedding of solvent molecules into electrode materials, thereby greatly improving the cycle performance and service life of lithium-ion batteries.

[0010] During the first charge and discharge process of a lithium battery, the electrode material and the electrolyte react at the solid-liquid interface, forming an interface film with a thickness of about 100-120nm at the negative electrode of the battery, namely the CEI film. The CEI film is an excellent conductor of lithium ions. Lithium ions can pass through the CEI film freely, but electrons cannot. During the charge and discharge process of a lithium battery, lithium ions will inevitably pass through the CEI film at the negative electrode of the lithium battery, so the CEI film has an impact on the battery performance.

[0011] By adopting the above technical solution, NN dimethyl trifluoroacetamide reduces the HOMO and LUMO energy levels of the additive molecule due to the presence of fluoride ions with strong electron-withdrawing ability, improves the oxidation resistance and reduction potential, and helps to form a good SEI film at the negative electrode; and the fluoride ions in NN dimethyl trifluoroacetamide combine with lithium ions to generate LiF, which increases the LiF content in the SEI film, significantly reduces the battery impedance, regulates the properties of the SEI film, and improves the low-temperature performance of the battery.

[0012] The central electronegativity of the sulfur atom in the center of methanedisulfonic acid methylene is strong, and the reduction potential on the negative electrode surface is significantly higher than the intercalation potential of the solvated lithium ion, and the Li2S and ROSO formed on the negative electrode surface 2 The SEI film component of Li effectively reduces the impedance of the SEI film, and the resulting SEI film is more stable, maintaining a longer stable overpotential while maintaining a similar lithium battery extraction / insertion mode.

[0013] The addition of lithium difluorophosphate makes the SEI film and ECI film contain PO bond compounds and more Li2CO3, which effectively reduces the CEI impedance. At the same time, the formed SEI film also contains more PO bonds and more inorganic components (Li2O, LiF), which is conducive to the formation of a denser SEI film and can inhibit the growth of lithium dendrites and improve the charge and discharge cycle stability.

[0014] The Si-O bond energy of trimethylsilylphosphite is greater than that of CO bond energy, and it can form a relatively stable SEI / CEI film at both the positive and negative electrodes and reduce impedance. Moreover, if trimethylsilylphosphite is not completely consumed during the formation process, it can react with HF produced by the hydrolysis of LiPF6 during the cycle process, reduce the dissolution of transition metals, reduce interfacial impedance, and improve battery performance.

[0015] On the one hand, hexamethyldisilazane can remove H2O or HF, thereby inhibiting the decomposition of the electrolyte itself and improving the electrochemical performance; on the other hand, the groups contained in hexamethyldisilazane preferentially undergo oxidative decomposition before the solvent, or produce coordination reactions with H2O or HF, thereby participating in the construction of a stable and durable SEI film.

[0016] The present invention uses a specific ratio of NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane to coordinately construct an inorganic component-rich, low-impedance, high-stability, thin and dense SEI / CEI film, which can effectively alleviate the lithium battery under low temperature conditions due to Li + The diffusion coefficient in the positive / negative electrode materials is low, the charge transfer and desolvation processes are slow, and the viscosity of the electrolyte increases and the wettability is poor at low temperatures, resulting in problems such as difficulty in charging, poor safety performance, capacity attenuation and severe battery polarization. The low temperature performance of lithium batteries is improved.

[0017] Furthermore, the weight ratio of the NN dimethyl trifluoroacetamide to lithium difluorophosphate is (4-5):1.

[0018] Furthermore, the weight ratio of the trimethylsilyl phosphite to hexamethyldisilazane is 2:1.

[0019] By adopting the above technical solution and optimizing the ratio, the low-temperature performance of lithium batteries can be further improved.

[0020] Furthermore, the organic solvent includes ethylene carbonate, ethyl methyl carbonate, trifluoroacetate, and fluoroether in a volume ratio of (8-11):(4-7):(2-5):(1-3).

[0021] By adopting the above technical solution, ethylene carbonate has good film-forming properties and a high dielectric constant, and is an indispensable part of commercial electrolytes. Using ethyl methyl carbonate and ethylene carbonate as a co-solvent can improve the low-temperature performance of lithium batteries.

[0022] Trifluoroacetate and fluoroether are added to ethyl methyl carbonate and ethylene carbonate as co-solvents. Among them, trifluoroacetate has a wider liquid range, lower viscosity, and a wider electrochemical window. As a co-solvent, it can effectively improve low-temperature conductivity and low-temperature capacity retention. Fluoroether and Li + The low binding energy and low viscosity further improve the low temperature performance of lithium batteries and have good flame retardant properties.

[0023] Furthermore, the organic solvent also includes propionitrile, and the volume ratio of propionitrile to ethylene carbonate is 1:20.

[0024] Furthermore, the lithium salt comprises lithium difluorooxalatoborate and lithium difluorosulfonyl imide in a weight ratio of (15-20):1.

[0025] By adopting the above technical solution, the structure of lithium difluorooxalatoborate can be regarded as a half-molecule test of lithium battery OB and lithium battery F4, combining the excellent low-temperature performance of lithium battery F4 and the excellent film-forming property of lithium battery OB. Lithium difluorooxalatoborate can form an HF-free SEI film, inhibiting the formation of lithium dendrites, so that the lithium battery has high conductivity and high capacity retention rate at low temperature. Lithium difluorosulfonyl imide has high ionic conductivity and Li + The migration number is large and the charge transfer impedance is low, which helps to form a LiF-rich SEI film, and can improve the low-temperature, fast-charging and rate performance of lithium batteries.

[0026] Furthermore, the diaphragm is a composite diaphragm, and the preparation method thereof is as follows:

[0027] 1) Mixing ethyl orthosilicate, ammonia water and anhydrous ethanol to obtain a mixed solution;

[0028] 2) Spread the polyethersulfone fiber membrane flat and soak it in the mixed solution;

[0029] 3) After soaking for 24 hours, take out, ultrasonically clean and dry to obtain a composite diaphragm.

[0030] Furthermore, the ratio of tetraethyl orthosilicate, ammonia water and anhydrous ethanol in the mixed solution is (8-12) g tetraethyl orthosilicate: 50 L ammonia water: 50 L anhydrous ethanol.

[0031] By adopting the above technical solution, polyethersulfone and silica are used to construct the structure of the fiber diaphragm through an in-situ growth process, so that silica is evenly coated on the surface of the polyethersulfone fiber, giving full play to the heat resistance and stability of polyethersulfone itself, and at the same time, the presence of silica gives the composite diaphragm flame retardant properties. In addition, the fibers in the diaphragm are wrapped by silica particles, thereby improving the wettability of the diaphragm to the electrolyte, and at the same time, the affinity of the large number of hydroxyl groups on the surface to the electrolyte is also improved, the diaphragm becomes more "solid", less prone to decomposition, and the voltage resistance is improved, and the electrochemical stability window of the composite diaphragm is increased.

[0032] The polyethersulfone fiber membrane can be purchased commercially or can be homemade.

[0033] Furthermore, the positive electrode sheet is one or more of lithium cobalt oxide, lithium nickel manganese cobalt ternary material, lithium iron phosphate, and lithium manganese oxide, and the negative electrode sheet is graphite and / or silicon.

[0034] In a second aspect, the present application provides a processing technology for a lithium battery for an electric bicycle, which adopts the following technical solution.

[0035] A processing technology for a lithium battery structure for an electric bicycle comprises the following steps:

[0036] S1. Weigh the lithium salt, organic solvent, cyclic sultone and additives according to a preset ratio;

[0037] S2. In an inert atmosphere, adding a lithium salt to an organic solvent until the lithium salt is completely dissolved in the organic solvent to obtain an initial mixed solution;

[0038] S3. Adding an additive to the initial mixed solution to obtain an electrolyte;

[0039] S4. Stack the positive electrode sheet, the negative electrode sheet and the separator in the order of positive electrode sheet, separator and negative electrode sheet, and then wind them to obtain a battery cell; place the battery cell in an outer packaging steel shell, inject the electrolyte into the outer packaging, and obtain a battery after vacuum packaging, standing, pre-discharging and aging processes.

[0040] In summary, this application has the following beneficial effects:

[0041] This application uses a specific ratio of NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane to coordinate and cooperate to construct an inorganic-rich, low-impedance, high-stability, thin and dense SEI / CEI film, which can effectively alleviate the problems of lithium batteries under low temperature conditions, such as the low diffusion coefficient of Li+ in the positive / negative electrode materials, slow charge transfer and desolvation process, increased electrolyte viscosity and poor wettability at low temperatures, resulting in difficulty in charging, poor safety performance, capacity decay and severe battery polarization, thereby improving the low-temperature performance of lithium batteries. The battery capacity retention rate of the obtained lithium battery at -40°C can reach 72-85%, and the battery capacity retention rate at -85°C can reach 42-53%. DETAILED DESCRIPTION

[0042] The present application is further described in detail below with reference to the embodiments.

[0043] Raw materials and intermediate preparation examples

[0044] raw material

[0045] The raw materials in the examples of this application can be obtained from commercial sources:

[0046] NN dimethyltrifluoroacetamide, analytical grade;

[0047] Methylene methanedisulfonate, analytical grade;

[0048] Lithium difluorophosphate, analytical grade;

[0049] Trimethylsilylphosphite, analytical grade;

[0050] Hexamethyldisilazane, analytical grade;

[0051] Ethylene carbonate, analytical grade;

[0052] Ethyl methyl carbonate, analytical grade;

[0053] Trifluoroacetate, analytical grade;

[0054] Fluorinated ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (F-EPE), analytical grade;

[0055] Propionitrile, analytical grade;

[0056] Lithium difluorooxalatoborate, analytical grade;

[0057] Lithium difluorosulfonyl imide, analytical grade;

[0058] Ethyl orthosilicate, analytical grade;

[0059] Ammonia, analytical grade;

[0060] Anhydrous ethanol, analytical grade.

[0061] Preparation Example

[0062] Preparation Example 1

[0063] A composite diaphragm, the preparation method of which is as follows:

[0064] 1) Mix 8 g of tetraethyl orthosilicate, 50 L of aqueous ammonia and 50 L of anhydrous ethanol to obtain a mixed solution;

[0065] 2) Dissolve the polyethersulfone resin particles in N,N-dimethylacetamide solvent, heat to 60°C and stir for 6 hours to completely dissolve the polyethersulfone resin particles in the solvent, let stand for 8 hours to obtain a transparent spinning solution. Use electrospinning to spin, collect the electrospun film on aluminum foil, spin for 8 hours, obtain a film, remove the film and dry it at 80°C to obtain a polyethersulfone fiber membrane;

[0066] Lay the polyethersulfone fiber membrane flat and soak it in the mixed solution;

[0067] 3) After soaking for 24 hours, take out, ultrasonically clean and dry at 80°C to obtain a composite diaphragm with a thickness of 15 μm.

[0068] Preparation Example 2

[0069] The difference from Preparation Example 1 is that in Preparation Example 2, the amount of ethyl orthosilicate is 12 g.

[0070] Preparation Example 3

[0071] The difference from Preparation Example 1 is that in Preparation Example 3, the amount of ethyl orthosilicate is 14 g.

[0072] Performance Testing

[0073] The flame retardant performance of the diaphragm was tested. The diaphragm was cut into fiber membrane disc samples with a diameter of 16 mm. The samples were ignited with an open flame for 2 seconds, and the state of the remaining fiber membrane was observed to determine its flame retardant performance. The test results are shown in Table 1.

[0074] The electrochemical stability window of the diaphragm was tested by using anodic linear voltammetry. The test results are shown in Table 1.

[0075] Table 1 Diaphragm performance test results

[0076]

[0077] Examples 1-3

[0078] A lithium battery structure for an electric bicycle, and a preparation method thereof is as follows:

[0079] S1. Weigh the lithium salt, organic solvent, cyclic sultone and additive according to the ratio in Table 2;

[0080] S2. In an inert atmosphere of nitrogen, the lithium salt is added to the organic solvent until the lithium salt is completely dissolved in the organic solvent to obtain an initial mixed solution;

[0081] S3. Adding an additive to the initial mixed solution to obtain an electrolyte;

[0082] S4. The positive electrode sheet, the negative electrode sheet and the separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer steel shell, the electrolyte is injected into the outer package, and the battery is obtained after vacuum packaging, standing, pre-discharging and aging steps;

[0083] The diaphragm comes from Preparation Example 1; the positive electrode is a lithium-nickel-manganese-cobalt ternary material, and the negative electrode is graphite.

[0084] Table 2 Raw material ratio table of Examples 1-3 (kg)

[0085]

[0086] The organic solvent includes ethylene carbonate, ethyl methyl carbonate, trifluoroacetate, and fluoroether in a volume ratio of 10:5:3:2;

[0087] The lithium salt includes lithium difluorooxalatoborate and lithium difluorosulfonyl imide in a weight ratio of 15:1;

[0088] The additives include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 4:1.5:1:2:1.5.

[0089] Example 4

[0090] Different from Example 2, the additives in Example 4 include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 3:2:0.8:2.5:1.

[0091] Example 5

[0092] Different from Example 2, the additives in Example 5 include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 5:1:1.2:1.5:2.

[0093] Example 6

[0094] Different from Example 2, the additives in Example 6 include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 5:1:1:1.5:2.

[0095] Example 7

[0096] Different from Example 2, the additives in Example 7 include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 5:1:1:2:1.

[0097] Example 8

[0098] Different from Example 2, the organic solvent in Example 8 includes ethylene carbonate, ethyl methyl carbonate, trifluoroacetate, fluoroether, and propionitrile in a volume ratio of 10:5:3:2:0.5.

[0099] Example 9

[0100] Different from Example 8, the organic solvent in Example 9 includes ethylene carbonate, ethyl methyl carbonate, and fluoroether in a volume ratio of 10:5:2.

[0101] Example 10

[0102] Different from Example 8, the lithium salt in Example 10 is lithium difluorooxalate borate.

[0103] Embodiment 11

[0104] Different from Example 8, the lithium salt in Example 11 is lithium difluorosulfonyl imide.

[0105] Examples 12-13

[0106] Different from Example 8, the diaphragms in Examples 12-13 are from Preparation Examples 2-3, respectively.

[0107] Embodiment 14

[0108] Different from Example 8, the diaphragm in Example 14 is a polyethersulfone fiber membrane with a thickness of 15 μm.

[0109] Comparative Example

[0110] Comparative Example 1

[0111] Different from Example 1, the additives in Comparative Example 1 include methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 1.5:1:2:1.5.

[0112] Comparative Example 2

[0113] Different from Example 1, the additives in Comparative Example 2 include NN dimethyl trifluoroacetamide, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 4:1:2:1.5.

[0114] Comparative Example 3

[0115] Different from Example 1, the additives in Comparative Example 3 include NN dimethyl trifluoroacetamide, methylene disulfonate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of 4:1.5:2:1.5.

[0116] Comparative Example 4

[0117] Different from Example 1, the additives in Comparative Example 4 include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, and hexamethyldisilazane in a weight ratio of 4:1.5:1:1.5.

[0118] Performance Testing

[0119] The lithium batteries obtained in the examples and comparative examples were tested for low temperature discharge performance. The test results are shown in Table 3.

[0120] Testing method: Charge the battery at 25℃ with a current of 0.5C, leave it for 5 minutes, and then discharge it at 0.2C to 2.5V. Record this capacity as C1. Charge the battery at 0.5C again, and then leave it at -40℃ and -85℃, respectively, and start discharging at 0.2C. Record this capacity as C2 and C3 respectively.

[0121] The capacity retention rate of the battery at -40°C is: C2 / C1×100%;

[0122] The capacity retention rate of the battery at -85°C is: C3 / C1×100%.

[0123] Table 3 Lithium battery low temperature performance test results

[0124]

[0125] Combining Examples 1-14 with Comparative Examples 1-4 and Table 3, it can be seen that the capacitance retention rates of the batteries obtained in Examples 1-14 at -40°C and -85°C are better than those of Comparative Examples 11-4, which indicates that the lithium battery obtained in the present application has better low-temperature performance.

[0126] Combining Example 2, Examples 4-7 and Comparative Examples 1-4, and Table 3, it can be seen that the type and ratio of additives have a significant effect on the capacitance retention rate of the battery at low temperatures, among which the type and ratio of additives in Example 7 are optimal. This may be because NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane within the ratio range specified in the present application cooperate to construct an inorganic component-rich, low-impedance, high-stability, thin and dense SEI / CEI film, which effectively alleviates the lithium battery under low temperature conditions due to Li + The diffusion coefficient in the positive / negative electrode materials is low, the charge transfer and desolvation processes are slow, and the viscosity of the electrolyte increases and the wettability is poor at low temperatures, resulting in charging difficulties and capacity attenuation, which improves the low-temperature performance of lithium batteries.

[0127] Combining Example 2 with Examples 8-9 and Table 3, it can be seen that organic solvents will also affect the low-temperature performance of lithium batteries, among which the ratio in Example 8 is the best.

[0128] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lithium battery structure for an electric bicycle, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, characterized in that: The electrolyte comprises 75-90 parts by weight of an organic solvent, 8-15 parts by weight of a lithium salt and 1-5 parts of an additive; The additives include NN dimethyl trifluoroacetamide, methylene disulfonate, lithium difluorophosphate, trimethylsilyl phosphite, and hexamethyldisilazane in a weight ratio of (3-5):(1-2):(0.8-1.2):(1.5-2.5):(1-2); The weight ratio of NN dimethyl trifluoroacetamide to lithium difluorophosphate is (4-5): 1; The weight ratio of trimethylsilyl phosphite to hexamethyldisilazane is 2:1; The organic solvent includes ethylene carbonate, ethyl methyl carbonate, trifluoroacetate, and fluoroether in a volume ratio of (8-11):(4-7):(2-5):(1-3); The organic solvent also includes propionitrile, and the volume ratio of propionitrile to ethylene carbonate is 1:

20.

2. A lithium battery structure for an electric bicycle according to claim 1, characterized in that: The lithium salt includes lithium difluorooxalatoborate and lithium difluorosulfonyl imide in a weight ratio of (15-20):

1.

3. A lithium battery structure for an electric bicycle according to claim 1, characterized in that: The diaphragm is a composite diaphragm, and its preparation method is as follows: 1) Mixing ethyl orthosilicate, ammonia water and anhydrous ethanol to obtain a mixed solution; 2) Spread the polyethersulfone fiber membrane flat and soak it in the mixed solution; 3) After soaking for 24 hours, take out, ultrasonically clean and dry to obtain a composite diaphragm.

4. A lithium battery structure for an electric bicycle according to claim 3, characterized in that: The ratio of tetraethyl orthosilicate, ammonia water and anhydrous ethanol in the mixed liquid is (8-12) g tetraethyl orthosilicate: 50 L ammonia water: 50 L anhydrous ethanol.

5. The lithium battery structure for an electric bicycle according to claim 1, characterized in that: The positive electrode sheet is one or more of lithium cobalt oxide, lithium nickel manganese cobalt ternary material, lithium iron phosphate, and lithium manganese oxide, and the negative electrode sheet is graphite and / or silicon.

6. A processing technology for a lithium battery for an electric bicycle according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh the lithium salt, organic solvent, cyclic sultone and additives according to a preset ratio; S2. In an inert atmosphere, adding a lithium salt to an organic solvent until the lithium salt is completely dissolved in the organic solvent to obtain an initial mixed solution; S3. Adding an additive to the initial mixed solution to obtain an electrolyte; S4. The positive electrode sheet, the negative electrode sheet and the separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell; The battery cell is placed in an outer steel shell, the electrolyte is injected into the outer shell, and the battery is obtained after vacuum packaging, standing, pre-discharging, and aging processes.

Citation Information

Patent Citations

  • Non-aqueous electrolyte for lithium iron phosphate battery

    CN102593517A

  • Electrolyte and lithium-ion battery containing same

    CN105845983A

  • Preparation method and application of lithium-ion-imprinted polyethersulfone composite membrane

    CN106902654A

  • Electrolyte and lithium ion battery

    CN113054252A